Mortality in the North Dublin Union During the Great Famine - Timothy W. Guinnane; Cormac Ó Gráda (Yale University, Economic Growth Center, 2001)
Responsibility for the tremendous excess mortality associated with the Great Irish Famine of 1846-51 is a continuing topic of debate. One view blames an inadequate government response for much of the tragedy. These debates are hampered by a lack of detailed information on how well relief efforts performed at a local level. Excess mortality ranged from one quarter of the entire population in parts of the west to negligible levels along much of the eastern coastline. Much of this cross-section variation reflects relative wealth. But another theme in the historiography stresses the importance of sympathetic or negligent local figures such as a landlord or priest. This study addresses the question of local agency with a case study of the North Dublin Union, the administrative unit responsible for administering the Irish poor law in the northern half of Dublin city and some adjacent parishes. North Dublin Union is unusual for the quality of its surviving administrative records. We use those records to study the Union's day-to-day functioning during the famine and to estimate mortality rates in the workhouse during the crisis. We find that the tremendous mortality of the North Dublin workhouse inmates during the famine primarily reflects the crisis outside the workhouse's walls; the guardians and managers did reasonably well in preserving human life under these trying circumstances.
Keywords: N33; J19; I39; 330; Ireland; famine; mortality; workhouses; Sterblichkeit; Unterernährung; Armutsbekämpfung; Irland